Competitive concurrence of surface wrinkling and dewetting of liquid crystalline polymer films on non-wettable substrates. Issue 42 (11th October 2017) - Song, Sung E.; Choi, Gwan H.; Yi, Gi-Ra; Yoo, Pil J.
Abstract : Liquid crystalline thin films coated on non-wettable substrates undergo multiple film-instabilities, which are manifested as concurrent occurrence of dewetting and wrinkling. Abstract : Polymeric thin films coated on non-wettable substrates undergo film-instabilities, which are usually manifested as surface deformation in the form of dewetting or wrinkling. The former takes place in fluidic films, whereas the latter occurs in solid films. Therefore, there have rarely been reports of systems involving simultaneous deformations of dewetting and wrinkling. In this study, we propose polymeric thin films of liquid crystalline (LC) mesogens prepared on a non-wettable Si substrate and apply a treatment of plasma irradiation to form a thin polymerized layer at the surface. The resulting compressive stress generated in the surface region drives the formation of wrinkles, while at the same time, dipolar attraction between LC molecules induces competitive cohesive dewetting. Intriguing surface structures were obtained whereby dewetting-like hole arrays are nested inside the randomly propagated wrinkles. The structural features are readily controlled by the degree of surface cross-linking, hydrophilicity of the substrates, and the LC film thickness. In particular, dewetting of LC mesogens is observed to be restricted to occur at the trough regions of wrinkles, exhibiting the typical behavior of geometrically confined dewetting. Finally, wrinkling–dewetting mixed structures are separated from the substrate in the form of free standing films to demonstrate the potential applicability as membranes.